THE ROLE OF ISLAMIC HIGHER EDUCATION IN IMPROVING SUSTAINABLE ECONOMIC DEVELOPMENT THROUGH ISLAMIC ENTREPRENEURIAL UNIVERSITY - Sonita , Era; Miswardi, Miswardi; Nasfi, Nasfi (International Journal of Social and Management Studies, 2021)
As a religion, Islam is a vision and way of life in taking action. In the field of entrepreneurship, research has proven that religion has a close relationship in realizing economic development. The topic of the role of entrepreneurial universities has attracted the attention of researchers by enriching the literature. However, the discussion on the role of Islamic entrepreneurial universities in economic development is still minimal. The main objective of this paper is to explore Islamic tertiary institutions as religious-based universities that can contribute to economic development through religious-based entrepreneurial activities, with the method used in writing this article is a literature review. The discussion started with sustainable economic development, then how entrepreneurial universities have an impact on economic development. Then try to explain how the relationship between Islam and entrepreneurship and then what is the entrepreneurial condition that has existed so far in Islamic universities.